2022
DOI: 10.1155/2022/2559258
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Related Gene Signature: An Individualized Risk Prediction Model for Kidney Renal Clear Cell Carcinoma

Abstract: Background. There is much evidence that confirms the inextricable link between inflammation and malignancy. Inflammation-related regulators were involved in the progression of kidney renal clear cell carcinoma (KIRC). However, the predictive role of single gene biomarkers is inadequate, and more accurate prognostic models are necessary. We undertook the current research to construct a robust inflammation-related gene signature that could stratify patients with KIRC. Methods. The transcriptome sequencing data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…SPHK1, a kinase in sphingolipid metabolism, is recognized as a critical factor in the regulation of inflammatory response and cellular immunity. 27 For example, SPHK1 promoted inflammatory responses in renal clear cell carcinoma 28 and cerebral ischemia/reperfusion injury, 29 and its reduced levels alleviated inflammatory factor release in ethanol-intoxicated septic mice 30 and was involved in the ameliorative effect of atractylenolide-1 in mice with colitis. 31 The transcriptional activation of pro-inflammatory cytokines (IL-6), chemokines, and adhesion molecules requires the activation of SPHK1.…”
Section: Discussionmentioning
confidence: 99%
“…SPHK1, a kinase in sphingolipid metabolism, is recognized as a critical factor in the regulation of inflammatory response and cellular immunity. 27 For example, SPHK1 promoted inflammatory responses in renal clear cell carcinoma 28 and cerebral ischemia/reperfusion injury, 29 and its reduced levels alleviated inflammatory factor release in ethanol-intoxicated septic mice 30 and was involved in the ameliorative effect of atractylenolide-1 in mice with colitis. 31 The transcriptional activation of pro-inflammatory cytokines (IL-6), chemokines, and adhesion molecules requires the activation of SPHK1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work revealed that high expression of glutamate dehydrogenase 1 (GLUD1) is detrimental to the survival of renal cancer cells in unfavorable nutritional environments (such as amino acid deficiency) and is significantly associated with good prognosis in KIRC patients [ 18 ]. High expression levels of adenosine A2b receptor (ADORA2B) and solute carrier family 1 member 5 (SLC1A5) were also correlated with poor prognosis in KIRC patients [ 19 , 20 ]. Further, the high expression of ACAT1 (HR = 0.44), GLUD1 (HR = 0.41), SLC38A1 (HR = 0.61), and SLC38A2 (HR = 0.63) are significantly correlated with good prognosis in LGG patients, while high expression of AHR (HR = 1.78), ENO1 (HR = 1.69), HK2 (HR = 3.56), MTOR (HR = 1.71), NFATC2 (HR = 2.16), SLC16A4 (HR = 2.92), SLC1A5 (HR = 3.00), SLC36A4 (HR = 1.67), and XBP1 (HR = 1.82) are correlated with poor prognosis in LGG patients.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we screened out 22 inflammatory genes such as Gabbr1 , by univariate Cox regression and different expression analysis in the TCGA database. Gabbr1 was classical macrophage-related genes which have been confirmed to be the inextricable link between inflammation and ccRCC ( Kovaleva et al, 2016 ; Zhang et al, 2022 ). Other overlapped genes, such as FZD5 and STAB1, which are known as scavenger receptors also participate in carcinogenesis, and their potential functions in ccRCC need to be further revealed ( Katoh, 2007 ; Hollmén et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%